Bimetallic Au@Rh core–shell nanostars with plasmon-enhanced catalytic performance in hydrogen evolution reaction. Issue 9 (7th February 2023) - Wu, Xin; Zhu, Xingzhong; Kan, Caixia; Shi, Daning
Abstract : Bimetallic Au@Rh core–shell nanostructures exhibit outstanding plasmon-enhanced electrochemical activity and stability, surpassing commercial Pt/C toward the HER. Abstract : Boosting the electrocatalytic performance of non-Pt catalysts for the hydrogen evolution reaction (HER) is of great importance in the context of the high price and scarcity of Pt. In this work, we successfully synthesized bimetallic core–shell nanostructures with Au nanostars as cores and Rh clusters as shells (Au@Rh nanostars) based on a two-step wet-chemistry strategy. We have demonstrated that the interaction strength between Rh and intermediate(s) involved in the HER could be effectively manipulated due to the existence of a strong electronic effect in bimetallic Au@Rh nanostars. The results from FDTD simulation suggested that the E-M field enhancement of the Au@Rh nanostar is inferior to that of the Au nanostar but there is a more localized distribution between the Au core and Rh shell. Benefiting from the synergistic effect and the plasmon-induced accelerated molecular transformations, the Au@Rh nanostars manifest outstanding plasmon-enhanced electrochemical activity toward the HER with a low overpotential of 28.5 mV for achieving the current density of 10 mA cm −2, which surpasses the commercial Pt/C. Furthermore, the obtained Au@Rh nanostars exhibited remarkable stability during the durability test with only a 3 mV shift in HER polarization curves after 5000 potential cycles. This study provides a versatile strategy for designing bimetallic core–shell nanostructures with plasmon-enhanced electrocatalytic performance.